1995
DOI: 10.1111/j.1365-2885.1995.tb00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and elimination of clenbuterol in tissues and fluids of calves following prolonged oral administration at a growth‐promoting dose

Abstract: A pharmacokinetic study is described in which Friesian calves (n = 30) were treated orally with clenbuterol at 10 times the therapeutic dose. The study was designed to establish the distribution and elimination of clenbuterol from edible tissues, the major compartments of the eye and body fluids. Animals (n = 24) were dosed (10 micrograms/kg body weight) twice daily with clenbuterol for 21 days and slaughtered in groups of five (one untreated control animal per group) at 6 h and 1, 2, 4, 8 and 16 days after ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 10 publications
5
29
0
6
Order By: Relevance
“…Agonists were chosen as representative of the most abused growth promoters. The MPRL is consistent with the pharmacokinetics of ␤-agonists, such as clenbuterol [17] and ractopamine [18] in urine of farmed cattle, according to the proposed doses in feeds.…”
Section: Introductionsupporting
confidence: 69%
“…Agonists were chosen as representative of the most abused growth promoters. The MPRL is consistent with the pharmacokinetics of ␤-agonists, such as clenbuterol [17] and ractopamine [18] in urine of farmed cattle, according to the proposed doses in feeds.…”
Section: Introductionsupporting
confidence: 69%
“…Delayed elimination of ractopamine from retina is consistent with data from previous studies with clenbuterol 4,. 8,, 9 Another advantage of using retinal tissue was that this matrix contributed less interference than liver for the three MRM transitions (Figs 2 and 3), resulting in an improved limit of confirmation (see below). The same procedures described above were used to quantify ractopamine residues in retina (Table 2).…”
Section: Resultssupporting
confidence: 87%
“…The results obtained in the present study are consistent with clenbuterol concentrations recorded in calf liver, which was found to decrease from 46 ng/g on day 0 to 0.5 ng/g on day 14 of treatment cessation (Meyer and Rinke 1991 ). This study found the liver to be more suitable as a matrix for clenbuterol detection than urine and plasma as control matrices (Pleadin et al 2009 ), thus liver tissue being considered appropriate for clenbuterol abuse monitoring (Sauer et al 1995 ). The sensitivity and specifi city of the chosen sample preparation and LC-ESI/MS/MS analysis conditions allow for the unambiguous identifi cation and quantifi cation of the target analyte in all liver samples collected from experimental animals.…”
Section: Concentration Of Clenbuterol Residues In Liver According To supporting
confidence: 95%